(3TQM GdehLR aj GdefWbs - (3aVd GdOjf CHi GdMSf Ydj Hf aNQ GdOjf Hf GdHOjY GdHfOgis; (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, CaVd GdOjf CHh YHO Gddg,J (B646 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdHfOgi GdMeO ddg hHYO abO GdJeS efi LeY ef GdeJQOOjf Edi Cf CLeY dge TQMkG ddebOeI GdehSheI ddehLQ GdaUd GdChd GdYde s
(3BNQgG (B:s
(3jfJgi HTQM GdbjGS GdESJKfGFi Hbhdg (B: (3hEYde Efg EPG cGf CLRGA GdefaUdg CcKQ ef EKfjf hESJKfjJ fbjV LRA hGMO GfJL eJUdg eG fYI GdNdh ef GdCLRGA s
(3HgG fXGe GdJYbjHIs
(3QJHg GdTGQM Ydi CMO YTQ aUdGs
(3hQO GdYfhGf GdCUdi ai cX (B2 /1901s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs